Emotions in the Qualitative Research Process: Introduction to the Special Issue - Siouti, Irini; Ruokonen-Engler, Minna Kristiina (Forum, qualitative social research, 2025)
Emotions play an important role in the qualitative research process. They can both hinder and facilitate scientific inquiry. Scholars rooted in different traditions of qualitative interpretative methods have emphasized the need to reflect on researchers' subjectivity. Thus, we argue that reflexive approaches can offer a starting point for exploring emotions in the qualitative research process. In this article, we introduce the special issue on "Emotions in the Qualitative Research Process." We provide a brief insight into the topic and discuss different theoretical perspectives and methodological approaches. By focusing on the qualitative interview methods, we underline the importance of considering emotional reflexivity as a central element of interactive field research.